Structure of Mangrove Forest and Carbon Sequestration Potential in the Estuarine Region of the Somber River, Balikpapan Bay, Indonesia: A Preliminary Assessment - Hamdhani, Hamdhani; Paputungan, Mohammad Sumiran; Ritonga, Irwan Ramadhan; Suyatna, Iwan (Jurnal Ilmiah Perikanan dan Kelautan, 2026)
Graphical Abstract   Highlight Research Nine mangrove species were identified in the Somber River estuary, dominated by Rhizophora and Avicennia. The mangrove forest exhibited an average density of 1,444 trees/ha, DBH of 13.3 cm, and canopy cover of 62.04%. Litterfall production averaged 9.28 Mg/ha/year, resulting in an estimated carbon sequestration of 47.25 Mg CO₂-eq/ha/year. Carbon sequestration correlated strongly with canopy cover and tree density, but not with DBH, with the midstream segment showing the highest values.   Abstract Mangroves are included in East Kalimantan’s emission reduction programs, but carbon absorption data remain lacking due to limited studies. In Balikpapan Bay, particularly around the Somber River estuary, information on carbon accumulation rates is still limited. This study aimed to document the species composition, tree density, diameter at breast height (DBH), and canopy cover of mangrove forests, estimate their carbon sequestration capacity, and compare sequestration rates across the upstream, midstream, and downstream sections of the Somber River in Balikpapan City, Indonesia. Nine sampling stations were established along the river to represent each segment. At each, mangrove species were identified, tree density and canopy cover measured, and litterfall collected. Carbon sequestration was then estimated from litterfall-based Net Primary Productivity (NPP). Nine species were recorded, dominated by Rhizophora and Avicennia. The forest averaged 1,444 trees/ha, DBH of 13.3 cm, and 62.04% canopy cover. Midstream sites showed the highest density (1,533 trees/ha) and canopy cover (65.7%), though not in DBH. Litterfall averaged 9.28 Mg/ha/year (0.58–18.76), corresponding to 47.25 Mg CO₂-eq/ha/year, peaking midstream. Sequestration rates did not differ significantly among segments but correlated strongly with canopy cover, density, and DBH. This study provides initial estimates of mangrove carbon uptake in the Somber River estuary near the Kariangau industrial area, offering insights for management strategies to enhance blue carbon storage, provides externally relevant estimates and a structure-to-sequestration linkage that can guide restoration targets, carbon accounting, and coastal policy in working estuaries. Further research should quantify sediment carbon accumulation and consider species-specific differences to better inform restoration efforts.